Cost Management and Strategic Decision Making: The Role of Managerial Accounting - Susilowati, Endah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study investigates the integration of cost management and strategic decision-making, focusing on the role of managerial accounting. It aims to explore how advanced cost management techniques, particularly Activity-Based Costing (ABC), contribute to achieving competitive advantage and aligning with strategic objectives. The research employs a qualitative design, using case studies and interviews with senior managers and financial controllers in medium to large manufacturing firms. This approach provides detailed insights into the implementation and effectiveness of ABC and other cost management practices in strategic decision-making. The findings reveal that ABC enhances cost information accuracy, facilitating more informed strategic decisions regarding pricing, product mix, and process improvements. Top management support and a conducive organizational culture are crucial for successful ABC implementation. Firms that regularly update their cost management practices maintain accuracy and relevance in cost information. The balanced scorecard effectively aligns cost management with strategic objectives, improving strategic alignment and decision-making. Organizations should prioritize adopting ABC, ensure strong top management support, and foster a culture of innovation. Regular updates to cost management practices and investment in training programs enhance managerial competencies and decision-making. These findings provide valuable insights for practitioners and scholars, highlighting the strategic role of managerial accounting in driving competitive advantage.